A contrastive study of rhetorical devices in children’s songs in english and vietnamese - Nguyễn, Đỗ Hà Anh. (ĐHNN, 2016)
This thesis is designed to study the rhetorical devices in children‟s songs in English versus Vietnamese by means of descriptive and comparative methods. Both qualitative and quantitative analysis are conducted basing on the investigation of a corpus of 500 rhetorical devices (250 in each language) taken from 20th- century children‟s songs in both English and Vietnamese. These children‟s songs are mainly collected from books for children under the age of 16 and school music textbooks for children from class 1 to class 9. On the basis of contrastive analysis, this thesis is carried out to find out the similarities and differences in terms of rhetorical devices in children‟s songs in English and Vietnamese, namely lexical rhetorical devices (metaphor, metonymy, simile, personification) and phonetic rhetorical device (repetition). The study found that of all five rhetorical devices analyzed in the thesis, Repetition (phonetic rhetorical device) is by far the most popular one in both English and Vietnamese songs for children. As far as lexical rhetorical devices are concerned, all four lexical rhetorical devices are used more commonly in Vietnamese children‟s songs than in English ones, with the highest one belonging to Metaphor. With an eye to partly contributing to better teaching and learning English as a foreign language, specifically to the awareness of learners and composers in writing children‟s songs, some implications and ideas are also included.
Keywords: contrastive study , rhetorical devices, children’s songs; contrastive study; rhetorical devices; children’s songs